Inside Back Cover: Ternary PtRuPd/C Catalyst for High‐Performance, Low‐Temperature Direct Dimethyl Ether Fuel Cells (ChemElectroChem 10/2016). Issue 10 (26th September 2016) - Dumont, Joseph H.; Martinez, Ulises; Chung, Hoon T.; Zelenay, Piotr
Abstract : The Inside Back Cover picture illustrates a direct dimethyl ether fuel cell, which exhibits a performance comparable to that of the state‐of‐the‐art direct methanol fuel cells. More information can be found in the Full Paper by P. Zelenay and co‐workers onpage 1564 in Issue 10, 2016 (DOI:10.1002/celc.201600336 ).